ACADEMIC JOURNEY FROM CHINA TO MALAYSIA VIA AVID E-EDUCATION - Pravina, Manoharan; Soubakeavathi, Rethinasamy (2021)
The year 2020 and 2021 have been a year of pandemonium as the Covid-19 pandemic drastically affected all forms of human interaction and mobility from travel, work conditions, economic sector, to social activities. The education sector has not been immune to these changes and the last one and a half years has seen many learning institutions shifting their conventional face to face mode of engagement to a virtual platform. Border closures and total lockdown around the world meant restricted travel for many students studying abroad. Thus, universities around the world resorted to offering online courses for their local as well as international students. This paper aims to provide a detailed description on the collaboration between a Malaysian public university and the industry to develop a comprehensive start-up Educational Technology (EdTech) platform called Avid Education. The collaboration is aimed at providing undergraduate and postgraduate academic support for students in China intending to pursue studies at Malaysian universities. The paper focuses on the creation of the business model of the platform and the various layers that contribute towards its successful execution. The Avid Education employed the On Demand Business Model that was spurred by the increased demand in student applications from China. The business collaboration was first established between the university and the industry to develop the Avid Education online platform. MOUs were then signed with student recruitment agents from Malaysia and China and the university to ensure a legal and steady flow of students. Module writers were engaged based on their vast expertise in teaching undergraduate and postgraduate courses. Bilingual teaching assistants and tutors were also hired to help students with their writing process. Based on the requests, three main modules were created, namely the postgraduate proposal writing module, undergraduate music module and English language proficiency enhancement module. Learning on the platform is delivered in three folds. Firstly, there are weekly live lectures taught by the module writers themselves with the presence of a bilingual teaching assistant. The content of selected topics is complemented by pre-recorded videos that are presented in a bilingual team-teaching format. This is then followed by one-to-one tutoring sessions with a bilingual English-Mandarin speaking tutor to assist the students and enhance their understanding of the module. The tutors consist of senior students who are given the opportunity to put their learning into practice and earn some pocket money as well. Assessments are presented in the form of gamification to keep learners engaged. At the end of the programme, the students are awarded a certificate by the university to acknowledge their successful completion of the module. In addition to the creation of the multi-layered business model and financial benefits, this paper will also discuss the educational benefits based on the findings from the feedback received from the first batch of students and how it has doubled their chances of gaining acceptance into public universities in Malaysia.